PERAN PERCEIVED VALUE DALAM MEMODERASI PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN KULINER PONDOK JAWI LAHAT - Amaludin Amaludin; Melia Handayani; Saparudin Saparudin (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to conduct research to analyze (1) the effect of service quality and perceived value on customer satisfaction; (2) the effect of perceived value on consumer satisfaction; and (3) the effect of service quality on customer satisfaction moderated by perceived value. The research was conducted at Pondok Jawi Lahat. In this study, researchers used descriptive research with a quantitative approach, basically one of the existing methods. Collecting data with a questionnaire technique through validity and reliability tests. Data analysis used linear regression analysis and absolute difference test, and previously performed the classical assumption test. The results showed that service quality and perceived value had a significant effect on Pondok Jawi Lahat customer satisfaction. Perceived value is a moderating variable that can strengthen the effect of service quality on customer satisfaction. The higher the perceived value of the customer will further strengthen the effect of service quality on customer satisfaction.